Encountering missionary life and work : preparing for intercultural ministry - Steffen, Tom A., 1947-; Douglas, Lois McKinney, 1931- (Grand Rapids, MI : Baker Academic, 2008)
This new volume in the award-winning Encountering Mission series is for current and future missionaries. It provides practical guidance regarding getting ready for the mission field and the realities of life on the field. The authors are well qualified to write such a manual, each having served as a missionary for more than twenty years and each having taught missions in seminary.
The changing scene -- Remembering the past -- Understanding key ideas and terms -- Home-front preparations -- Decision making and the will of God -- Spiritual formation -- Personal readiness -- Ministry readiness -- Avenues to cross-cultural ministries -- Finding your niche -- Getting going -- On-field preparations -- What is culture? -- At home in the culture -- Culture and language acquisition -- Missionaries and their lives -- Women in missions -- Missionary families -- Crises in missions -- Reentry -- What's next?
Includes bibliographical references (pages 365-378) and indexes.
Keywords: Missions; Missionaries; Christianity and culture